Experimental and Numerical Study on Seismic Performance of Batter Pile Groups in Loose Sand: No subtitle - Hussain, Qassim I.; Al-Neami, Mohammed A.; Rahil, Falah H. (Civil Engineering Journal, 2025)
Pile foundations are critical for maintaining structural integrity under seismic loading, and batter piles, being inclined elements, offer enhanced resistance to combined vertical and lateral forces compared to conventional vertical piles. The objective of this study is to investigate the seismic performance of negative and positive batter pile groups in loose sand. The research employed experimental and numerical approaches: shaking table tests were conducted on 3×3 pile groups embedded in sand with a relative density of 31.2%, subjected to the El Centro and Kobe earthquakes, while finite element modeling was performed to validate the experimental outcomes. The analysis compared the responses of piles with batter angles of -5°, 0°, and +5° in terms of lateral displacement, vertical displacement, and acceleration. Findings revealed that negative battering substantially amplifies pile group displacements, as demonstrated by a 22.085% increase in maximum lateral displacement and a 23.061% rise in vertical displacement for the El Centro motion when the batter angle shifted from 0° to -5°. Conversely, positive battering reduced displacements by up to 4.765%. The novelty of this work lies in experimentally and numerically quantifying the seismic drawbacks of negative battered piles, thereby providing new insights for optimizing pile group design in seismic regions.